Successful Conservative Treatment of Cesarean Scar Pregnancy with Systemic Methotrexate Injection: A Case Report - H.M, Irwan Muhaeimin; Rahman, Irwan Taufiqur; Widad, Shofwal (JURNAL KESEHATAN REPRODUKSI, 2023)
Cesarean scar pregnancy (CSP) is a rare but life-threatening complication. It is the abnormal implantation of gestational sac into myometrium and fibrous scar of previous cesarean section. Its incidence is on rising trend due to increase in rate of cesarean section all over the world. A thirty one-year old third gravida presented at five weeks of gestation with complaints of vaginal spotting. She was diagnosed as a case of cesarean scar pregnancy (CSP) on ultrasonography. Conservative management of CSP was done successfully with the injection of systemic methotrexate. CSP pregnancy could be catastrophic, if not managed well in time. Management includes both surgical and medical options. The optimal management of caesarean section pregnancy should be individualized depending upon the hemodynamic status depending on patient’s hemodynamic profile, size of gestational sac, desire for future fertility, and patient’s preference.